The differences in quality of life between healthy and periodontal disease patients with SUD at lido rehabilitation center: an observational analytical study. - Effendi, Nadira Zahrani; Louisa, Marie; Theresia, Tiarma Talenta; Parorrongan, Chrisanty Anastasia; Putri, Anzany Tania Dwi; Putri, Resthie Rachmanta (Padjadjaran Journal of Dentistry, 2025)
Introduction: Drug abuse adversely affects oral health, leading to conditions such as xerostomia, caries, and periodontal disease. Periodontal disease can cause discomfort such as pain, bleeding gums, and tooth loss. These can negatively affect quality of life by impairing chewing, speech, and self-confidence. This study aims to analyze the differences in quality of life among healthy, gingivitis, and periodontitis patients with SUD (Substance Use Disorder) at the Lido Rehabilitation Center. Methods: This cross-sectional study was conducted at the Lido Rehabilitation Center in West Java in August 2024. A total of 101 SUD patients were recruited using purposive sampling based on predetermined inclusion and exclusion criteria. All participants underwent oral examinations and completed the WHOQOL-BREF questionnaire, which assesses quality of life across four domains: physical, psychological, social, and environmental. Periodontal disease was evaluated based on probing depth, bleeding on probing, and clinical attachment loss, with periodontal status serving as the independent variable and quality of life as the dependent variable. Statistical tests were performed to determine differences in quality of life among the healthy, gingivitis, and periodontitis groups. Results: A total of 63.4% of respondents were diagnosed with periodontal disease. Patients diagnosed as healthy had the highest mean score in the psychological domain (55,51 ± 15,47) compared to gingivitis and periodontitis patients (51,07 ± 12,85) and (47,68 ± 17,89) respectively. The Kruskal-Wallis test revealed a significant difference among the groups (p = 0.026), and Tukey's post-hoc test indicated a significant difference between gingivitis and periodontitis groups (p = 0.007). Conclusion: There is a difference in QoL among healthy, gingivitis, and periodontitis groups, especially in the psychological domain. Respondents with periodontal disease had lower quality of life scores compared to healthy respondents.